Solution structure of the stalk subunits E and G of the vacuolar ATPase from yeast and interaction studies of subunits E and G with the neighboring subunits - Sankaranarayanan Rishikesan (2012)
Subunit G of the yeast V-ATPase is observed to be an elongated protein with a maximum size and the radius of gyration as 8.0 nm and 2.7 nm, respectively (ARMBRÜSTER et al., 2003). In order to understand the structure of subunit G and its possible orientation with respect to the other stalk subunits, two constructs G1-58 and G61-101, were created. The structure of both, the N- and C-terminal domains were solved by solution NMR technique. Precipitation assays have suggested the interaction of subunit G and E on the N-termini of both the subunits (JONES et al., 2005). Thus the interaction of subunit G with its neighboring stalk subunits, including E and d, were studied using NMR spectroscopy and FCS. Subunit E is an essential component of the V1 assembly, as disruption of the gene on the yeast (Vma4) resulted in a disassembly of the V1VO complex (KANE et al., 2003). The N-terminus of subunit E (E1-69) was expressed, purified to homogeneity and the solution structure was studied through NMR spectroscopy. The C-terminus of subunit E, a predicted globular domain E133-222 was cloned, expressed and purified to homogeneity. Efforts were also taken to study the solution structure of the same through NMR spectroscopy. The first secondary structure of E133-222 was determined and the region forming the β-strands on the globular domain is presented.